2009
DOI: 10.1103/physrevlett.103.076101
|View full text |Cite
|
Sign up to set email alerts
|

High Island Densities in Pulsed Laser Deposition: Causes and Implications

Abstract: By studying metal growth on Pt(111), we determine the reasons for the high island densities observed in pulsed laser deposition (PLD) compared to conventional thermal deposition. For homoepitaxy by PLD with moderate energies ( < or approximately 100 eV) of the deposited ions, high island densities are caused by the high instantaneous flux of arriving particles. Additional nuclei are formed at high ion energies (> or approximately 200 eV) by adatoms created by the impinging ions. For heteroepitaxy, the island d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Alternatively, pulsed plasma sources, such as PLD, can also generate pulsed vapour fluxes [11,46]. Again, the pulsed character of deposition fluxes generated by PLD discharges has been used to control films nucleation [47] and growth [48] as well as to understand the dynamics of island coalescence and its effect of the film microstructural evolution during Volmer-Weber film growth [11].…”
Section: Strategies For Generation Of Highly Ionized and Pulsed Vapoumentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, pulsed plasma sources, such as PLD, can also generate pulsed vapour fluxes [11,46]. Again, the pulsed character of deposition fluxes generated by PLD discharges has been used to control films nucleation [47] and growth [48] as well as to understand the dynamics of island coalescence and its effect of the film microstructural evolution during Volmer-Weber film growth [11].…”
Section: Strategies For Generation Of Highly Ionized and Pulsed Vapoumentioning
confidence: 99%
“…PLD processes generate a highly ionized deposition flux with ion energies up to 300 eV [18]. These energetic ions affect both surface and subsurface layers and thus film nucleation and coalescence [3,15,28,29,112]. The broad ion energy distribution functions (IEDFs) make identification and understanding of the atomistic mechanisms that along with the modulated vapour flux determine the film microstructural evolution a non-trivial task.…”
Section: Dynamics Of Microstructural Evolution During Volmer-weber Thmentioning
confidence: 99%
“…For the preparation of thin film containing nanoscale structures (e.g., nanoparticles, nanowires, nanotubes) by using ns-pulsed laser deposition (PLD), a high-energy laser beam focused on a target induces the heating, melting, evaporation of a thin layer of the irradiated material (Aghaei et al, 2008), and thus the formation of plasma associated with the production of particle emission in front of the target (Alti & Khare, 2006;Trusso et al, 2005;Wang et al, 2009). The charged ions with energies between tens and hundreds of eV (Schmid et al, 2009) collide with ambient gas, and produce the charged nanoscale structures by the condensation process (Hirasawa et al, 2006;Muramoto et al, 1999;Seto et al, 2001Seto et al, , 2003, and finally are deposited on the substrate to form the thin film.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PLD under vacuum conditions, even at room temperature, results in a higher island nucleation density with respect to molecular beam epitaxy (MBE), thus allowing atom-by-atom deposition of films with a controlled layer-by-layer morphology. [9][10][11][12] Moreover, it is known that laser ablation in the presence of an inert background gas results in a spatial confinement of the expanding plasma favoring cluster formation due to increased collision rate with the surrounding gas molecules [13][14][15] and thus allowing deposition of preformed clusters and growth of cluster-assembled materials. 16 In this framework, the comprehension of the parameters affecting plasma expansion dynamics and their role in regulating the deposition process is fundamental for the synthesis and deposition of clusters and for the growth of cluster-assembled films with tailored properties.…”
Section: Introductionmentioning
confidence: 99%